"When Is Health Care Actually Going to Be Care?" The Lived Experience of Family Planning Care Among Young Black Women. Issue 7 (July 2021) - Logan, Rachel G.; Daley, Ellen M.; Vamos, Cheryl A.; Louis-Jacques, Adetola; Marhefka, Stephanie L.
Abstract : (Abstracted from Qual Health Res 2021;31:1169–1182) Family planning care (FPC) visits are intended to provide education and opportunities for women to obtain family planning services, including hormonal medications. Structural barriers, sociocultural barriers, and mistreatment by the health care system may perpetuate the numerous health inequities surrounding reproductive health and pregnancy among young Black women.